Application of Problem-Based Learning Model to Improve Problem Solving Ability - Rochana, Siti; Wahyuniar, Lilia Sinta; Mahdiyah, Umi (Pendidikan Matematika STKIP Kusuma Negara, 2022)
This study aims to improve the problem solving ability of class VIII junior high school students. This research was conducted after the preliminary study it was found that problem solving abilities were still relatively low. Observational shows that more than 50% of class VIII students of SMP Muhammadiyah 3 Depok have poor problem solving skills. Based on the theory put forward some expert of experts, the researchers decided to apply the problem-based learning model. This study uses classroom action research design with a target of 50% of students having a problem solving ability score above the Kriteria Ketuntasan Minimal (KKM). There are four stage of this research, namely planning, implementation, observation and reflection. The data collection technique using the test and non-test techniques. Data analysis using descriptive analysis of quantitative and qualitative analysis descriptive. From the results of the study, it was found that 77% of students had problem solving scores above the KKM. Besides that, it was found that student were able to work on the questions in a more structured manner and could better understand the questions given.